TRANSFORMING PUBLIC SPACES IN THE DIGITAL AGE: HOW TECHNOLOGY CHANGES THE FACE OF SOCIAL INTERACTION - Johni Eka Putra; Dedah Ningrum; Al-Afandi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This research examines the transformation of public space in the digital era and its impact on the patterns and quality of social interaction. Digital technology, especially the internet and social media, has played a significant role in revolutionizing the way individuals communicate and interact. Through a comprehensive literature analysis, this research illustrates how technology has enabled global connectivity, expanded social networks, and created new platforms for cultural expression and collaboration. On the other hand, this research also identifies challenges that arise as a result of these changes, such as social fragmentation, the decline in the quality of face-to-face interactions, and the complexity of digital privacy and ethical issues. This research highlights the importance of societal adaptation to new social norms and the development of digital literacy to effectively manage the impact of this transformation. Thus, this research not only provides insight into the role of technology in changing the face of social interaction but also emphasizes the need for a critical and reflective approach in dealing with these new dynamics.